Ignition of water-coal fuel droplets during radiative-convective- conductive heating in relation to boilers operating on the technology of circulating fluidized bed. (1st August 2022) - Kuznetsov, G.V.; Syrodoy, S.V.; Kostoreva, Zh.A.; Yu. Malyshev, D.; Purin, M.V.
Highlights: Inert material significantly accelerates the ignition of a drop of coal-water fuel. The effect of an inert material is most pronounced at moderate temperatures (Tg = 873 K). At high oxidizer temperatures, the inert material does not affect the ignition process. Inert material leads to dispersion of the near-surface layer of the fuel. Abstract: One of the most promising options for reducing anthropogenic heating of coal-fired power plants on the environment is the use of not homogeneous coal as the main fuel, but coal-water suspensions. But the combustion of coal-water fuels is associated with the solution of the problem of large values of the ignition delay times for such fuels. Therefore, an important task of great practical importance is the selection (or development) of technologies for combustion of coal-water suspensions in the furnaces of steam and coal-water boilers. The article presents the results of experimental studies of the coal-water fuel drops ignition processes. They were carried out in order to establish the temporal characteristics and conditions of ignition under conditions of a flare mode and combustion in a circulating fluidized bed of an inert material. According to the results of experiments, it was found that at moderate temperatures of the environment (Tg  ≤ 873 K), particles of inert material (sand) accelerate the ignition of coal-water fuel drops. With high-temperature heating, the ignition delay times for these two fuel combustion technologies are identical in relation to the combustion of coal-water fuels prepared from typical (for energy purposes) semi-anthracite and high-volatile A bituminous coal. Colloquium. The energy crisis in autumn 2021 showed the problem of the rapid transition of the world community from traditional thermal energy to the energy of non-traditional renewable energy generators (wind, sun, biomass). It became obvious that in the next few decades, developed countries will be forced to use coal as their main energy source. Therefore, at present, an urgent task is to reduce the concentration of anthropogenic oxides in the flue gases of coal-fired power plants. One of the most promising technological solutions to this problem is the combustion of coal in the composition of coal-water fuel (CWF). But the technologies of combustion of coal-water fuels in the furnaces of steam and hot water boilers have not yet been developed, mainly due to the problem of large values of the ignition delay times for droplets of such fuels. Therefore, furnace devices of the traditional design of the chamber type with flare combustion of CWF have not yet been developed. One of the promising technologies for the combustion of coal-water fuel can be the technology of a circulating fluidized bed of inert material. But the results of studies of the coal-water fuels drops ignition processes under conditions corresponding to combustion devices operating on the technology of a circulating fluidized bed have not yet been published.